Implementation of a didactic sequence based on socio-scientific controversies with Artificial Intelligence (AI) to promote scientific argumentation - Rodríguez-Malebrán, Mariano (2025)
The objective of the study is to design and implement a didactic sequence based on socio-scientific controversies, supported by the use of Artificial Intelligence (AI), in order to promote scientific argumentation among second-year secondary school students in Córdoba, Argentina. Framed within a Design-Based Research (DBR) approach, two iterative cycles (2023 and 2024) were carried out, including design, implementation, and analysis phases, allowing for adjustments to the proposal after the first cycle. The sample consisted of 37 students in the first cycle and 34 in the second, working in the subject of Biology with an emphasis on the cell and tissue engineering. The methodology combined participant observation, written records, and the analysis of argumentative responses structured according to Toulmin’s model, comparing productions completed with and without the support of ChatGPT. The results indicated improvements in the foundation of data and justifications, reflected in clearer conclusions; however, a decrease in the autonomous formulation of hypotheses and counterarguments was observed. In conclusion, the intervention strengthened argumentative skills, demonstrating the potential of AI to enrich educational practice and foster critical reflection on ethical and scientific dilemmas, despite some noted limitations in argumentative diversity and a certain dependence on technology.